Adoption of e-commerce with UTAUT model approach: A case study of the millenial generation in Jakarta - Margaretta, Devina; Putra , Ryan Caesar Dwi (Central Community Development Journal, 2025)
The E-Commerce industry has experienced significant growth in recent years. The continued use of e-commerce to improve the quality of life depends on several factors. Trust and Payment Methods have emerged as important factors influencing E-Commerce Adoption. This study examines the UTAUT factors of millennial consumers' E-Commerce Adoption in Jakarta by focusing on the mediating role of trust and the mediating role of Payment Methods. This study used a path analysis method with a quantitative approach. The research data were collected using a questionnaire with 181 millennial respondents who had made purchase transactions in e-commerce. This research analysis tool uses SEM-PLS. This study revealed that of the six variables studied, three had no significant effect, while three had a significant effect on E-Commerce Adoption in Jakarta.